The effect of budget tightness and internal audit on the perceived usefulness of management accounting systems. - DAHLAN, MUHAMMAD (IJRDO - Journal of Business Management, 2016)
The objective of this research is how to effect and measure the budget tightness and internal audit on the perceived usefulness of management accounting systems. Mail questionnaires were distrbuted to 149 stated-owned enterprise in Indonesia and than we have responcy rate of 85 Indonesia enterprise. Data validity and reliability of independent variable is valid and reliable. Hypothesis testing use regression analysis. The result show that positively effect of the budget tightness and internal audit on the perceived usefulness of management accounting systems. Base on research, characteristics of management accounting informations including of broadscope, timeliness, the level of aggregation and integrative nature can be support by the roles of implementation of tight budget and internal auditor’s function.